Heterologous Biosynthesis of the Fungal Sesquiterpene Trichodermol in Saccharomyces cerevisiae - Liu, Jianghua; Zhai, Yanan; Zhang, Yang; Zhu, Shuaiming; Liu, Gang; Che, Yongsheng (Frontiers in Microbiology, 2018)
Trichodermol, a fungal sesquiterpene derived from the farnesyl diphosphate pathway, is the biosynthetic precursor for trichodermin, a member of the trichothecene class of fungal toxins produced mainly by the genera of Trichoderma and Fusarium. Trichodermin is a promising candidate for the development of fungicides and antitumor agents due to its significant antifungal and cytotoxic effects. It can also serve as a scaffold to generate new congeners for structure-activity relationship (SAR) study. We reconstructed the biosynthetic pathway of trichodermol in Saccharomyces cerevisiae BY4741, and investigated the effect of produced trichodermol on the host by de novo RNA sequencing (RNA-Seq) and quantitative Real-time PCR analyses. Coexpression of pESC::FgTRI5 using plasmid pLLeu-tHMGR-UPC2.1 led to trichodiene production of 683 µg L−1, while integration of only the codon-optimized FgTRI5 into the chromosome of yeast improved the production to 6,535 µg L−1. Subsequent expression of the codon-optimized cytochrome P450 monooxygenase encoding genes, TaTRI4 and TaTRI11, resulted in trichodermol, with an estimated titer of 252 µg L−1 at shake flask level. RNA-Seq and qPCR analyses revealed that the produced trichodermol downregulated expression of the genes involved in ergosterol biosynthesis, but significantly upregulated the expression of PDR5 related to membrane transport pathway in S. cerevisiae. Collectively, we achieved the first heterologous biosynthesis of trichodermol by reconstructing its biosynthetic pathway in yeast, and the reconstructed pathway will serve as a platform to generate trichodermin analogues as potential candidates for agrochemicals and anticancer agents through further optimizations.